2019
DOI: 10.1186/s40862-019-0067-5
|View full text |Cite
|
Sign up to set email alerts
|

Learning proverbs through telecollaboration with Japanese native speakers: facilitating L2 learners’ intercultural communicative competence

Abstract: Telecollaboration has been considered to have great potential for the development of L2 learners' intercultural communicative competence (ICC), so an examination of what benefits L2 learners receive through telecollaboration is necessary. Also, L2 learners' use of culturally specific expressions, such as proverbs, has not been adequately investigated. The present study investigated the effects of telecollaboration on L2 learners' perceptions of their ICC knowledge and skills in relation to one type of verbal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The results showed that students' speaking, vocabulary, writing, reading, and grammar skills improved when communicating through text and speech because students double-checked vocabulary spelling and grammar. Students identified errors they made when communicating using text and speech and corrected them to ensure that others understood their intended meaning (Calogerakou and Vlachos, 2011 ; Chen and Yang, 2014 , 2016 ; Lewis and Schneider, 2015 ; Özdemir, 2017 ; Hirotani and Fujii, 2019 ; Jung et al, 2019 ; Sevy-Biloon and Chroman, 2019 ; Jamalai and Krish, 2021 ). In addition, students' listening skills improved after watching YouTube videos (Özdemir, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that students' speaking, vocabulary, writing, reading, and grammar skills improved when communicating through text and speech because students double-checked vocabulary spelling and grammar. Students identified errors they made when communicating using text and speech and corrected them to ensure that others understood their intended meaning (Calogerakou and Vlachos, 2011 ; Chen and Yang, 2014 , 2016 ; Lewis and Schneider, 2015 ; Özdemir, 2017 ; Hirotani and Fujii, 2019 ; Jung et al, 2019 ; Sevy-Biloon and Chroman, 2019 ; Jamalai and Krish, 2021 ). In addition, students' listening skills improved after watching YouTube videos (Özdemir, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…All studies point to the development of cultural interaction skills after students interacted and exchanged different cultural perspectives with partners (Calogerakou and Vlachos, 2011 ; Chen and Yang, 2014 , 2016 ; Lewis and Schneider, 2015 ; Özdemir, 2017 ; Hirotani and Fujii, 2019 ; Jung et al, 2019 ; Sevy-Biloon and Chroman, 2019 ). Communication (Chen and Yang, 2014 ; Lewis and Schneider, 2015 ; Hirotani and Fujii, 2019 ) and collaboration skills were also developed (Chen and Yang, 2014 ) in reviewed studies.…”
Section: Discussionmentioning
confidence: 99%
“…Axiom 7: There are various Teaching models for ICC development. There are tested teaching models to help learners develop their ICC: multi-strategy or integrated approach of conventional and traditional teaching while including culture during language classes (Tran & Duong, 2018;Liton, 2016;Romanov & Snegurova, 2017;Andryukhina, Fadeeva, & Negri, 2017;Mitchell, Pardinho, Yermakova-Aguiar, & Meshkov, 2015); explicit teaching such as providing a list of terms then followed by discussion for gradual formation of ICC (Szerszeń & Romanowski, 2018;Hirotani & Fujii, 2019;Holmes & O'Neill, 2012); and use of literature (Aksyonova & Akhtambaev, 2014;DevísArbona & Silvia-Maria, 2015) to examine the motifs contained in any country's folk literature, link them together employing similarity (to local culture), which would greatly facilitate ICC during language classes. Teachers should ponder on utilizing texts and "literary translation" activities for intercultural learning development.…”
Section: Axiomsmentioning
confidence: 99%
“…There needs to be a shift from traditional to intercultural teaching practice in ESL/EFL (Jin, 2014;Hirotani & Fujii, 2019). Updating the content of the discipline allows possibilities to explore the use of the English language in different contexts (Andryukhina, Fadeeva, & Negri, 2017;Galante, 2015).…”
Section: Axiomsmentioning
confidence: 99%
“…ABPs are strategies to encourage educational processes with technology and use communication skills through aspects of tele-collaboration (Clavel-Arroitia 2019); that turns the classroom into an active space to reinforce creativity and critical thinking supported by technological innovation and entrepreneurial activities (Gutiez 2016;Best et al 2017); uses online communication tools where students meet and collaborate on projects under guided instruction, teacher education experiences show that web 2.0 allows collaborative work, helps promote in-depth learning, strengthens content understanding and skills development communicative and digital (Hirotani and Fujii 2019;Astall and Cowan 2016).…”
Section: Introductionmentioning
confidence: 99%